2006
DOI: 10.1080/00087114.2006.10797892
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal studies of three species of Bidens (L.) (Asteraceae)

Abstract: -The chromosomal numbers of three species of Bidens were determined based on an analysis of somatic metaphases. The species studied were Bidens pilosa L., Bidens subalternans DC and Bidens alba (L.) DC, all of which belong to the Bidens pilosa species complex. The three species have a similar morphology: Bidens pilosa and B. subalternans are widely distributed in agricultural areas, in disturbed habitats and along roadsides, whereas B. alba occurs only along the seacoast. Bidens pilosa has 2n=72 and B. subalte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Following, materials were stained with leuco-basic fuchsin in the dark at room temperature for 2 h and treated with 1 % pectinase at room temperature for 1 h to separate the connected cells. Root-tips were spread on a slide and squashed in a drop of 45 % acetic acid and then observed under a microscope (Grombone-Guaratini et al 2006). Totally, 16 cells of var.…”
Section: Methodsmentioning
confidence: 99%
“…Following, materials were stained with leuco-basic fuchsin in the dark at room temperature for 2 h and treated with 1 % pectinase at room temperature for 1 h to separate the connected cells. Root-tips were spread on a slide and squashed in a drop of 45 % acetic acid and then observed under a microscope (Grombone-Guaratini et al 2006). Totally, 16 cells of var.…”
Section: Methodsmentioning
confidence: 99%
“…Plants constitute a vital part of the world’s primary health care [ 1 ]. Bidens pilosa , an underutilized plant species is a member of the Asteraceae family [ 2 , 3 ] widely distributed around the world [ 4 ]. It is rich in phenolic compounds that are of great medical significance [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to previous studies, D. pinnata has a 2n = 4x = 64 karyotype [ 30–32 ], and C. bipinnatus has a 2n = 2x = 24 karyotype [ 30 , 33 ]. However, in the genus Bidens , many plants have a similar morphology, and there are tetraploid and hexaploid populations [ 26 , 34 ]. Previous reports showed that B. alba has a 2n = 4x = 48 karyotype [ 26 , 35 ], and our karyotype analysis of B. alba by fluorescence in situ hybridization (FISH) delivered the same result ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%